DESIGN OF WATER DISTRIBUTION SYSTEM IN LELES DISTRICT GARUT - RAHMA LAILA (NIM : 15313018), DINA
Leles is one of 42 districts in Garut Regency and still unserved of clean water access provided by PDAM Tirta Intan until now. PDAM Tirta Intan plans to develop water supply system specifically for Leles and Kadungora districts in 2019 with the raw water resources taken from Cigunungagung and Ciharus river. This study aims to design water distribution system in Leles district. The service period is planned in 2 periods for 20 years with the service areas that are prioritized are on 8 villages. The quantity of water demand in phase I and II are projected to reach 66 L/sec and 107 L/s, respectively. The water distribution system applied in Leles district is using gravity and pumped system. In this study, there are three alternatives of water distribution pathway that are hydraulically analyzed using EPANET 2.0. The best alternative is selected by using Simple Additive Weighting (SAW) method. This study also designs a reservoir with a capacity of 2.008 m3. The budget plan is estimated to reach Rp 9.803.520.059,- with economical feasibility calculated in number of Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PBP) are Rp 10.921.588.354-, 14,41% and 15,65 years. The most common risk of this project is the loss of water during operation. The sustainability analysis of this project is characterized by improvements in sanitation quality, reduction of waterborne diseases and involvement of local government, yet community. Life cycle analysis is also carried out mainly in the energy consumption of the pump. The environmental evaluation states that the project will have an important impact on traffic problem, the quality of clean water in the event of a leak, protests from the community on pre-construction and construction and the possibility of job opportunities. The uncertainty analysis on this project is settled on clean water usage standards, leakage rate, number of customers and number of PBP from initial investment.